Effects of aging on left atrial reservoir, conduit, and booster pump function: a multi-institution acoustic quantification study. Issue 3 (1st March 2001) - Spencer, K T; Mor-Avi, V; Gorcsan, J; DeMaria, A N; Kimball, T R; Monaghan, M J; Perez, J E; Weinert, L; Bednarz, J; Edelman, K; Kwan, O L; Glascock, B; et al.
Abstract : OBJECTIVE: To assess the feasibility of measuring left atrial (LA) function with acoustic quantification (AQ) and then assess the effects of age and sex on LA reservoir, conduit, and booster pump function. PATIENTS AND SETTING: 165 subjects without cardiovascular disease, 3–79 years old, were enrolled by six tertiary hospital centres. INTERVENTIONS: Continuous LA AQ area data were acquired and signal averaged to form composite waveforms which were analysed off-line. MAIN OUTCOME MEASURES: Parameters of LA performance according to age and sex. RESULTS: Signal averaged LA waveforms were sufficiently stable and detailed to allow automated analysis in all cases. An age related increase in LA area was noted. LA reservoir function did not vary with age or sex. All parameters of LA passive and active emptying revealed a significant age dependency. Overall, the passive emptying phase accounted for 66% of total LA emptying ranging from 76% in the youngest to 44% in the oldest decade. LA contraction accounted for 34% of atrial emptying in all subjects combined with the older subjects being more dependent on atrial booster pump function. When adjusted for atrial size, there were no sex related differences in LA function. CONCLUSIONS: LA reservoir, conduit, and booster pump function can be assessed with automated analysis of signal averaged LA area waveforms. As LA performance varies with age, establishment of normal values should enhance the evaluation of pathologic states in which LA function is important.